TINJAUAN LITERATUR KONDISI PSIKOLOGIS REMAJA PENDERITA KANKER - Yunike, Yunike; Kusumawaty, Ira; Virgonita Iswindari Winta, Mulya (Berajah Journal, 2024)
Adolescent cancer is a significant health problem that can have a serious impact on their lives. Adolescent cancer is influenced by several factors such as genetics, environment, and lifestyle. Other prevention and treatment measures have been identified that facilitate the prevention process. This review aims to provide an understanding of the psychology of adolescents who experience cancer. This study is a narrative review taken from 3 databases namely google scholar, scopus, and sciencedirect and assessed with critical appraisal so that 10 articles were reviewed with 9 quantitative articles and 1 systematic review article. Based on the results of the review, factors that influence the level of distress of adolescents due to cancer, the quality of life of adolescents diagnosed with cancer and the resilience of adolescents with cancer were obtained. Adolescents with cancer face unique challenges in their lives, which affect various aspects, including physical, emotional, social and psychological. Social support from family, peers and community is crucial in helping adolescents overcome the challenges they face. Strong support networks can improve resilience and quality of life. Psychological interventions and psychological support are integral to the care of adolescents with cancer. Counselling, therapy and healthy coping strategies can help them to manage stress, anxiety and depression.